Is transcutaneous oxygen and carbon dioxide monitoring indispensable in short- and long-term therapeutic management of non-reconstructable lower critical limb ischemia? - Melillo, E; Nuti, M; Pedrinelli, R; Buttitta, F; Balbarini, A (Minerva cardioangiologica, 2006)
The aim of this study was to evaluate the capacity of transcutaneous partial pressure of O(2) (TCpO(2)) and CO(2) (TCpCO(2)) to predict clinical response to pharmacological treatment in short- and long-term follow-up of unreconstructable critical limb ischemia (CLI) treated with prostanoids; to suggest a diagnostic and therapeutic algorithm able to define the possibility of prostanoid therapy in unreconstructable CLI at high risk of limb loss. Twenty-six consecutive patients with CLI (21 with distal trophic lesions, 31 symptomatic limbs) considered unreconstructable after peripheral angiography and with a history of type 2 diabetes mellitus underwent daily parenteral Iloprost treatment for 2-3 weeks. Transcutaneous gas-analytic monitoring (TGM) in non-reconstructable CLI treated with Iloprost divided patients into 2 groups: early responders (ER) with increased TcpO(2) and normalization of TcpCO2, and non responders (NR) with unchanged TcpO(2) and TcpCO(2) parameters. In the NR who underwent a second cycle of Iloprost within a few months of the first, TGM further divided the patients into another subgroup of late responders (LR) with TcpO(2) and TcpCO(2) similar to the ER group and a subgroup of NR, who, after pharmacological treatment failure, should undergo eventual surgical re-timing and/or spinal cord stimulation in a final attempt to save the limb. In the short-term follow-up of CLI, a marked reduction in supine/dependent TcpO(2) and a marked increase in supine TcpCO(2) at the symptomatic forefoot proved to be significant predictors of major amputation risk. In the long-term follow-up period, TGM showed that, in ER and in LR, the favourable effect of pharmacological therapy observed in the first 6 months will disappear over the next 6 months, suggesting an algorithm of 2- to 3-week cycles of prostanoid therapy repeated every year. In NR treated with surgical and/or alternative therapies who did not undergo major amputations, prolonged instrumental TGM will provide a constant evaluation of metabolic parameters, thus providing the possibility to save the limb with additional pharmacological therapy.